Effects of oil shocks on EMU exports: technological level differences - Martin Hodula; Bohdan Vahalík (Review of Economic Perspectives, 2017)
This article provides some new empirical perspectives on the relationship between oil-market fluctuations and technological structure of EMU export. We rely on a time-varying parameter VAR model to capture the reaction of different technological structures of EMU export to various oil-market innovations in the period 2002-2015. Our results can be summarized as follows: (1) increase in crude oil production is likely to reduce oil prices and therefore increases all EMU exports due to lower production and transportation costs; (2) increase in global demand is more likely to be transmitted to goods with higher added value; (3) high-tech exports decrease in the first months after the global demand shock as a result of a delayed investment decision process; (4) increasing oil prices yield only marginal effect on EMU export.
Keywords: 330; EMU; export; technological structure; TVP-VAR